Metamorphosis of the theme of exile: tradition, revolution, and continuity from chivalric novels to the Opera dei Pupi (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
Chivalric literature is characterized by a long-lasting imagery, which links medieval and Renaissance literary texts and nineteenth- and twentieth-century forms of popular theater (Opera dei Pupi and cunto). A recurring feature of this imagery is the exile, which leads the knight to clash with power and go to distant lands. The paper will firstly examine the macroscopic features of exile in the chivalric imaginary, trying to highlight its elements of continuity and innovation, and then it will focus on a specific case: the story of Malaguerra, adopted son of Rinaldo, which Giusto Lodico created in his Storia dei paladini di Francia by mixing traditional texts and components and which has known new life in the scripts and performances of the Opera dei Pupi. It is a particularly representative case for observing the mixture of tradition and innovation in the chivalric exile.
Keywords: Chivalric literature; Opera dei Pupi; exile; rebellion; Malaguerra